Pengaruh Jaringan Sosial Terhadap Keberlanjutan Usaha Pedagang Konveksi di Pasar Simpang Aur Kota Bukittinggi - Ressa Safitri Rahmadani; Resdati Resdati (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Convection businesses are part of Micro, Small, and Medium Enterprises (MSMEs) that play an important role in creating jobs and providing livelihoods, especially in the Simpang Aur Market, Bukittinggi. This study aims to analyze the influence of social networks on the sustainability of convection businesses based on Mark Granovetter's social network theory and John Elkington's sustainability theory. The research uses a quantitative inferential approach with a population of 720 traders. The sampling technique used is purposive sampling, resulting in 88 samples. Data collection was carried out through questionnaires and documentation, then analyzed using correlation tests, simple linear regression, t-tests, and determination coefficients. The results show that there is a significant influence of social networks on business sustainability (r = 0.545; t = 6.028; p < 0.05), with a contribution of 29.7%. In conclusion, social networks have a significant influence on the sustainability of convection businesses.